2013
DOI: 10.5539/ijps.v5n1p112
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Social Activities outside the Home on Life Satisfaction among Elderly People Living Alone

Abstract: This study aims to test the following two hypotheses. First, the life satisfaction of the elderly is not directly affected by their resident status. Second, guided by activity theory and symbolic interaction theory, social activities outside the home (paid work, unpaid work, and hobby/leaning activity) have a greater effect on life satisfaction for elderly people living alone than those living with family members. Participants were 1,774 elderly people who had participated in courses for the elderly to learn v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…Regarding health-related factors, they were found to have poor physical health. Earlier studies also pointed out the problems with the well-being of women living alone and reported the need for appropriate interventions [37]. Living with family was a positive factor on the psychological well-being of female heads of house.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding health-related factors, they were found to have poor physical health. Earlier studies also pointed out the problems with the well-being of women living alone and reported the need for appropriate interventions [37]. Living with family was a positive factor on the psychological well-being of female heads of house.…”
Section: Discussionmentioning
confidence: 99%
“…A study on LS amongst elderly people living in Australia, found that social, health, security of life, residence, acceptance and adjustment influences the level of LS among the elderly [ 20 ]. Studies also showed that residential status have a negligible impact on LS [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of Okamoto 19 , the association between satisfaction with life and paid work was not found in the investigated elderly men, this association was obtained only for women. In the study of Nakahara 20 , this association was not significant for the elderly who performed paid work, only for the elderly who held unpaid work. This author argued that the permanence of older people in paid activities would be the result of low socioeconomic status and, therefore, it is not a positive influence to the well-being in old age.…”
Section: Introductionmentioning
confidence: 83%
“…As for life satisfaction, we found out that elderly people who continued to exercise paid employment in old age reported being more satisfied with life in its various dimensions (with life in general, with the social, cognitive and functional aspects and others) compared to those who stopped working. In a study by Nakahara 20 , Table 3. Odds ratios and 95% confidence intervals for association of the permanence in the labour market with sociodemografics characteristics, presence of chronicles pathologies and life satisfaction (N = 614).…”
Section: Domain Satisfactionmentioning
confidence: 99%